School‐age outcomes of infants at risk for autism spectrum disorder. Issue 6 (9th October 2015) - Miller, Meghan; Iosif, Ana‐Maria; Young, Gregory S.; Hill, Monique; Phelps Hanzel, Elise; Hutman, Ted; Johnson, Scott; Ozonoff, Sally
Abstract : Studies of infants at risk for autism spectrum disorder (ASD) have proliferated, but few of these samples have been followed longer‐term. We conducted a follow‐up study, at age 5.5–9 years, of younger siblings of children with ASD (high‐risk group, n = 79) or typical development (low‐risk group, n = 60), originally recruited as infants. Children with ASD were excluded because of the focus on understanding the range of non‐ASD outcomes among high‐risk siblings. Using examiner ratings, parent ratings, and standardized assessments, we evaluated differences in clinical outcomes, psychopathology symptoms, autism symptoms, language skills, and nonverbal cognitive abilities. After adjusting for covariates, the high‐risk group had increased odds of any clinically elevated/impaired score across measures relative to the low‐risk group (43% vs. 12%, respectively). The high‐risk group also had increased odds of examiner‐rated Clinical Concerns (CC) outcomes (e.g., ADHD concerns, broader autism phenotype, speech‐language difficulties, anxiety/mood problems, learning problems) relative to the low‐risk group (38% vs. 13%, respectively). The high‐risk group with CC outcomes had higher parent‐reported psychopathology and autism symptoms, and lower directly‐assessed language skills, than the Low‐Risk Typically Developing (TD) and High‐Risk TD groups, which did not differ. There were no differences in nonverbal cognitive skills. For some in the high‐risk group, clinical concerns persisted from early childhood, whereas for others clinical concerns were first evident at school‐age. Results suggest continued vulnerability in at least a subgroup of school‐age children with a family history of ASD and suggest that this population may benefit from continued screening and monitoring into the school‐age years. Autism Res 2016, 9: 632–642 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.